2021
DOI: 10.3390/educsci11070347
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning during the COVID-19 Pandemic: A Topic Modeling Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused significant disruption to teaching and learning activities at all levels. Faculty, students, institutions, and parents have had to rapidly adapt and adopt measures to make the best use of available resources, tools and teaching strategies. While much of the online teaching pedagogies have been theoretically and practically explored to a limited extent, the scale at which these were deployed was unprecedented. This has led a large number of researchers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 94 publications
(91 reference statements)
0
43
0
2
Order By: Relevance
“…We found that students majoring in more "theoretical" subjects such as humanities, education and law felt much more satisfied with their ERL experience than students majoring in practical fields such as engineering and engineering trades, physical sciences and arts. This is not surprising since, as already pointed out, while theoretical material could potentially be delivered effectively using virtual sessions, offering laboratory sessions or workshops remotely is quite challenging, since practical sessions are hands-on by definition [45,89]. Several other researchers [10,51,[90][91][92] also found that the replacement of conventional classes with ERL was often problematic for courses where laboratory presence is required (e.g., engineering, medicine, instrumental music, drawing, electronics).…”
Section: Lack Of Hands-on and Practical Trainingmentioning
confidence: 95%
“…We found that students majoring in more "theoretical" subjects such as humanities, education and law felt much more satisfied with their ERL experience than students majoring in practical fields such as engineering and engineering trades, physical sciences and arts. This is not surprising since, as already pointed out, while theoretical material could potentially be delivered effectively using virtual sessions, offering laboratory sessions or workshops remotely is quite challenging, since practical sessions are hands-on by definition [45,89]. Several other researchers [10,51,[90][91][92] also found that the replacement of conventional classes with ERL was often problematic for courses where laboratory presence is required (e.g., engineering, medicine, instrumental music, drawing, electronics).…”
Section: Lack Of Hands-on and Practical Trainingmentioning
confidence: 95%
“…This will be the core challenge for university teaching in the next decade and this paper provided some empirical hints as well as in-depth thoughts regarding that issue from Germany. This has to be compared and complemented with experiences from other countries [54,55,[62][63][64][65][66] as well as other education areas [67]. In total, university lecturers are challenged globally to make the most out of the harsh and limiting circumstances experienced in the 2020/2021 timeframe due to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible improvements and optimizations of e-learning strategies are the adoption of proactive learning strategies, with more interactions with teachers and colleagues or better models for providing practical classes, an appropriate internet connectivity, clear instructions to carry out assessments, or a fair number of assessments [30]. Additionally, a diversified offer of e-learning options may be beneficial, such as lectures, tutorials, workshops, conferences, journal clubs, online sessions, or combinations of these [50,51].…”
Section: Studies Exclusively Involving Pharmacy Studentsmentioning
confidence: 99%
“…Questionnaires seem to be an appropriate and suitable tool to evaluate pharmacy students' perceptions of e-learning. Questionnaires/surveys were developed to evaluate the attitudes of pharmacy students based on different types of questions/topics, such as: "what do think about your attitude toward e-learning", "I would prefer to have online learning to become the new normal", "I feel comfortable to actively communicate with my classmates and instructors online", "I feel that taking courses online will help me to remember/master them better", "I prefer in-class approach as it provides a lot of interaction with my instructors and students" or "Distance learning has increased my collaborative work with my colleagues, whether in the dormitory or remotely" [7,33,50,51]. The questionnaires/questions were heterogeneously developed.…”
Section: Limitations Of the Selected Studies Practical Implications A...mentioning
confidence: 99%